Reflexiones sobre el cuidado de sí como categoría de análisis en salud (2009)
ABSTRACT: This article ponders about self care in health as a category of analysis related to collective health. Such category enables us to understand how subjects participate actively in the promotion and development of daily practices which provide care. Within this framework, self care involves the relation of inner dialogues of human beings with themselves, their bodies and the setting where they perform their daily activities. Such a reflection privileges the micro in human beings' experience, the socio-cultural background, the world of everyday life as scenery of economic and social reproduction where interactions become real. Such reflection also points out the intersubjective relations which enable the emergence of knowledge socially built regarding the maintenance and care of health.